A steady-state pool of calcium-dependent actin is maintained by Homer and controls epithelial mechanosensation - Kenji Matsuzawa; Makoto Suzuki; Yuma Cho; Ryoya Fujinaga; Junichi Ikenouchi (Proceedings of the National Academy of Sciences, 2025)
Epithelial cells are inherently contractile and in homeostasis, tissue integrity is maintained by balancing the uneven contractile forces in neighboring cells at the cell–cell interface. By contrast, epithelial cells can utilize an imbalance in contractile force to communicate various information to induce tissue-wide response as in wound healing. Contractility is generated and processed at the apical junctional complex (AJC) by the dynamic behavior of the actin cytoskeleton. Calcium signaling can pattern cellular responses based on its reach and amplitude and the actin cytoskeleton is supported by its wide ranging effects on actin regulators. Calcium transients regulate various cell behaviors associated with actin remodeling, such as in damage response and developmental morphogenesis. Here, we report that calcium maintains an adaptive pool of AJC-associated actin that is sensitive to tension and encoded by calcium dynamics. For this, the recently identified epithelial polarity module Homer-MUPP1/PatJ is required. Homer regulates calcium signaling in various tissue contexts through interaction with numerous components of the endoplasmic reticulum (ER) and plasma membrane (PM) calcium signal toolkit. Knockout of either Homer or MUPP1/PatJ attenuated tension-induced calcium response and severely disrupted wound healing migration, which is dependent on guidance input through AJC tension. We also show that Homer is integral to early embryonic neurodevelopment as its suppression causes failure of neural tube closure. Our findings highlight the critical role of localized calcium dynamics on AJC actin remodeling and cellular behavior, elucidating the means of tissue coordination through intercellular tension.